2020
DOI: 10.1016/j.dhjo.2020.100889
|View full text |Cite
|
Sign up to set email alerts
|

The wellbeing of working-age adults with and without disability in the UK: Associations with age, gender, ethnicity, partnership status, educational attainment and employment status

Abstract: BackgroundFew population-based studies have examined the association between disability and personal wellbeing (PWB) among working-age adults. Objective/HypothesisTo determine: (1) the magnitude of differences in wellbeing between working-age adults with and without disability in contemporary samples representative of the UK population; and (2) whether the size of any observed differences between people with and without disability is moderated by age, gender, ethnicity, partnership status, educational attainme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 27 publications
1
21
0
3
Order By: Relevance
“…The current study has shown that the KPB project has the potential to enhance wellbeing and reduce loneliness for the general population. This supports providing more KBP card exchanges in more contexts in the future, particularly during periods when people are vulnerable to mental or physical difficulties due to social isolation or natural disasters (Emerson et al, 2020), although sufficiently powered randomised controlled trials are required to provide more robust evidence on efficacy. It could be an inexpensive intervention to improve public wellbeing and reduce loneliness worldwide for people under the current social isolation orders due to the Covid-19 pandemic (Clair et al, 2021;Grover et al, 2020).…”
Section: Implications For Practicementioning
confidence: 93%
“…The current study has shown that the KPB project has the potential to enhance wellbeing and reduce loneliness for the general population. This supports providing more KBP card exchanges in more contexts in the future, particularly during periods when people are vulnerable to mental or physical difficulties due to social isolation or natural disasters (Emerson et al, 2020), although sufficiently powered randomised controlled trials are required to provide more robust evidence on efficacy. It could be an inexpensive intervention to improve public wellbeing and reduce loneliness worldwide for people under the current social isolation orders due to the Covid-19 pandemic (Clair et al, 2021;Grover et al, 2020).…”
Section: Implications For Practicementioning
confidence: 93%
“…However, there is an evolving body of knowledge suggesting that disability-related inequalities in wellbeing do not reflect a direct negative impact of impairment, but rather that demographic characteristics and exposure to social determinants of poor health play a major role in the negative association between disability and wellbeing. 29 …”
Section: Introductionmentioning
confidence: 99%
“…As we transition during the pandemic, it is imperative that people who are at high risk are supported to re-participate in society given the greater restrictions they have experienced during the pandemic and can do so without bias or discrimination. For instance, a pertinent area to consider is the return to work given the importance of employment for health and wellbeing [ 15 ].…”
Section: Discussionmentioning
confidence: 99%